Death Row Phenomenon as an Inhumane Punishment in Human Rights - Alfian Barik, Zidny; Afifah, Wiwik; Widarsadhika Wisnumurti, Rahadyan (International Conference of Innovation and Community Engagement, 2024)
The Death Row Phenomenon is a psychological and physical condition experienced by death row inmates who endure years of waiting for their execution. During this waiting period, inmates face isolation, leading to deep mental stress and suffering. Even while on death row, there is uncertainty regarding the execution of their sentences. This study aims to examine the Death Row Phenomenon as a form of inhumane punishment. The research method employed is normative legal research, utilizing both a statutory approach and a conceptual approach. The treatment of death row inmates during this waiting period clearly violates human rights principles, as it is deemed inhumane and degrading, constituting a form of torture. The Death Row Phenomenon illustrates that the death penalty involves not only physical execution but also the prolonged waiting process, which can trigger various forms of suffering. Inmates often experience mental disorders, long-t]erm depression, and anxiety, further deteriorating their lives. The uncertainty surrounding the timing of the execution adds to their psychological burden, creating a prolonged atmosphere of terror. The Death Row Phenomenon constitutes inhumane punishment due to the legal uncertainty that prevents death row inmates from exercising their rights to fair treatment under the law. The discriminatory treatment, which differentiates the sentencing of death row inmates from that of other prisoners, represents a form of discrimination and indicates the presence of torture and double punishment, as death row inmates undergo both imprisonment and the death sentence itself.